SAR-Assisted Energy-Efficient Hybrid ADCs - Kent Edrian Lozada; Dong-Jin Chang; Dong-Ryeol Oh; Min-Jae Seo; Seung-Tak Ryu (IEEE Open Journal of the Solid-State Circuits Society)
The distinct advantages of low power consumption and hardware compactness make SAR ADCs especially appealing in scaled CMOS technologies, garnering significant attention. The residue left on the capacitor digital-to-analog converter (CDAC) after conversion in the SAR ADC negates the need for complex residue extraction circuits. This crucial feature has inspired numerous SAR-assisted architectural variations, employed in a range of applications from high resolution to high speed. This article introduces several energy-efficient hybrid ADC architectures that incorporate SAR ADCs as their sub blocks, including the following: SAR-assisted subranging SAR, which saves DAC switching power and can detect skew errors for time-interleaved ADCs; SAR-flash hybrid for energy-efficient high-speed conversion; SAR-assisted dual-residue pipelined ADC, which eliminates the stringent requirement for residue gain accuracy; and SAR-assisted delta–sigma modulator (DSM) with digital-domain noise coupling, which reduces the number of required analog integrators.